Opportunities and challenges of targeting c-Met in the treatment of digestive tumors - Zhang, Zhengchao; Li, Dong; Yun, Heng; Tong, Jie; Liu, Wei; Chai, Keqiang; Zeng, Tongwei; Gao, Zhenghua; Xie, Yongqiang (Frontiers in Oncology, 2022)
At present, a large number of studies have demonstrated that c-Met generally exerts a crucial function in promoting tumor cells proliferation and differentiation in digestive system tumors. c-Met also mediates tumor progression and drug resistance by signaling interactions with other oncogenic molecules to activate downstream pathways. Therefore, c-Met is a promising target for the treatment of digestive system tumors. Many anti-tumor therapies targeting c-Met (tyrosine kinase inhibitors, monoclonal antibodies, and adoptive immunotherapy) have been developed in digestive system tumors. Some drugs have been successfully applied in clinic, but most of them are limited in clinical application due to their efficacy and complications. In order to promote the clinical application of targeting c-Met drugs in digestive system tumors, it is necessary to further explore the mechanism of c-Met action in digestive system tumors and optimize the anti-tumor treatment of targeting c-Met drugs. Through reading a large number of literatures, the author systematically reviewed the biological functions and molecular mechanisms of c-Met assotiated with tumor, and summarized the current status of targeting c-Met in the treatment of digestive system tumors, so as to provide new ideas for the treatment of digestive system tumors.